The impact of agricultural policy evolution on long-run grain market projection - Lee, Suhwan; Ohler, Adrienne; Thompson, Wyatt (Applied Economic Perspectives and Policy, 2024)
Long-run projections are crucial for climate change policies, food security, and agricultural productivity, yet these projections often overlook recently identified patterns in how trade policies and domestic support evolve as countries develop. The grain
Keywords: Long-Run Modeling; Market Projections; Policy Projections; Agricultural Policy